Legal protection of older persons from neglect: the effectiveness of the continental criminal law system and the illusion of the protective function = Protección jurídica de las personas mayores contra la negligencia : la eficacia del sistema de derecho penal continental y la ilusión de la función protectora - Sitarz, Olga (Revista de victimología, 2024)
This article seeks to answer the question of whether the modern legal systems of selected countries allow a criminal justice response in the case of neglect of basic duties towards older persons. The consequences of neglect may be far reaching for that category of victims because of their psychophysical properties. Solutions have been proposed to increase the effectiveness of protecting older persons from neglect. Given the subsidiarity of criminal law, these calls are of a universal and systemic nature. They refer not only to the proposals for changes in the field of law, but they draw attention to the need for a debate across wider society on caring for the elderly and meeting their needs.